Loop- and cascade-based co-design of an agroecological dairy farming system in Burkina Faso - Ouattara, Songdah Désiré; Sib, Ollo; Sanogo, Souleymane; Sodre, Étienne; Vall, Eric (2024)
The growing demand for dairy products in West Africa, together with recent changes in the price of imported milk powder, provides an opportunity to intensify and develop local milk production, collection and processing (Sib et al., 2017; Duteurtre and Vidal, 2018; Vall et al. 2021). In Burkina Faso, as throughout West Africa, most of the milk production comes from extensive pastoral and agro-pastoral systems, with semi-intensive and intensive systems also contributing to a lesser extent (Vall et al., 2021). The local dairy value chain has to contend with low cow productivity, the seasonal nature of production - which makes collection difficult - and the relatively low capacity of processing facilities. Faced with this seasonality in production, which is largely due to feed shortages in the dry season, farmers tend to diversify their cow supplementation strategies during that period, with greater storage of crop residues, the use of agro-industrial by-products (AIBPs) and expensive feed concentrates that are beyond the reach of most farmers. In addition to these resources, interest in forage production on farms is beginning to grow. For many years, forage crops were encouraged by research and development, but rarely introduced, as they were less suited to farmers' needs as long as natural grazing was still available to feed livestock (Landais and Lhoste, 1990; Vall et al., 2017). In addition, research into forage crops was confined to research stations, with very few applications in the real world where uptake occurs. Today, the situation is changing. The landscape is being reshaped, pastures are increasingly inaccessible, land pressure is increasing, Burkina Faso's inherently poor soil quality is worsened by farming practices that are detrimental to its sustainability, climate uncertainties are growing, with an increase in the frequency of extreme weather events, and transhumance is increasingly impeded. As a result, livestock farmers are looking for ways to adapt and sustainably increase their self-sufficiency in forage and organic manure, but need technical and organizational support to do so.